Recovery of essential oils from carobs through various extraction methods - Orphanides, Antia; Goulas, Vlasios; Chrysostomou, M.; Gekas, Vassilis (My University, 2011)
The carob tree Ceratonia siliqua is abundant in the Mediterranean countries, thrives in dry climates and its fruit contains important essential oils with antioxidant properties. In the present work, various methods of extraction have been applied on carob powder in order to recover the essential oils. The results of the experiments help in to optimize the appropriate method of recovery, among ultrasonic bath, Soxtec extraction, and conventional (hexane) extraction and hydrodistillation.
Keywords: Antioxidant activity; Carob tree; Carobs; Essential oils; Extraction; Hydrodistillation; Soxtec